Melestarikan Multikulturalisme Budaya Kesenian Simalungun Di Era Digitalisasi - Hasian Napitu; Sunggul Gultom; Anggiat Sinurat; Ulung Napitu (Departement of Mathematics Education, 2023)
The Simalungun tribe is one of the Batak tribes in the Simalungun Regency, North Sumatra Province. The Simalungun tribe is located between two cultures, namely the Toba Batak tribe and the Karo Batak tribe. Because the area of residence of the Simalungun Batak tribe is between the territories of the two Batak tribes, the Simalungun language is almost similar to the Toba and Karo languages. The Simalungun people's livelihood system is farming rice and corn, because rice is the daily staple food and corn is an additional food if the rice yield is insufficient. Buying and selling is carried out by bartering, the language used is the dialect.